The influence of job satisfaction and work motivation on organizational commitment among Catholic religious education teachers - Din Oloan Sihotang; Ermina Waruwu; Aman Simaremare (Indonesian Journal of Educational Development (IJED), 2026)
This study examines the influence of job satisfaction and work motivation on organizational commitment among Catholic Religious Education teachers in Indonesia. Despite extensive research on organizational commitment, few studies have examined these relationships in faith-based educational contexts. Using a quantitative approach with path analysis, the study involved 208 teachers selected through proportional random sampling. Data were collected using validated Likert-scale questionnaires and analyzed using IBM SPSS. The findings reveal that job satisfaction and work motivation have a positive and significant influence on teachers' organizational commitment, both individually and simultaneously, accounting for 64.2% of the variance. Teachers who experience supportive working conditions, fair recognition, and strong intrinsic motivation tend to demonstrate higher emotional attachment, loyalty, and dedication to their schools. These findings highlight the importance of leadership strategies that enhance both satisfaction and motivation to sustain long-term teacher commitment in faith-based educational institutions.